Risk factors associated with congenital defects that alter hearing or vision in children born in the city of Bogotá between 2002 and 2016. (November 2019) - Manotas, M.; Sarmiento, K.; Ibañez-Morantes, A.; Suárez-Obando, F.; Gelvez, N.; López, G.; Ayala-Ramírez, P.; Angel, J.; Prieto, J.; Tamayo, N.; Puentes, S.; Rodríguez, C.; et al.
Abstract: Introduction: Congenital defects affecting the auditory and visual capacity of newborns represent a public health problem as they result in substantial disability, directly impacting the quality of life of newborns and their families. Objective: To evaluate risk factors associated with congenital defects that alter hearing or vision in newborns in the city of Bogotá between 2002 and 2016. Method: Data from the Bogotá Birth Defects Surveillance and Follow-up Program was used, which consolidated data regarding 167 ECLAMC study (Estudio Colaborativo Latino Americano de Malformaciones Congénitas, in spanish) variables in a case-control design to identify risk factors for birth defects after parents provided signed informed consent. Cases were defined as any newborn (alive or stillborn) with a weight greater than 500 g with any visual or hearing abnormality. Controls were defined as newborn in the same hospital and month with no birth defects. Groups were formed according to the case presentation as follows: isolated eye anomaly, isolated ear anomaly, polymalformative, syndromic, and teratogenic. Results: In total, 402, 657 births were reviewed, of which 968 cases had some congenital defects that alter hearing or vision. An association was found between the presence of defects and prematurity, as well as between syndromic cases and increasing maternal age. When comparing cases and controls with the risk of having a birth defect, multiparity had an odds ratio (OR) of 1.47 (95% CI: 1.27–1.71), acute respiratory infection had an OR of 2.41 (95% CI: 1.04–5.58), low maternal education level had an OR of 1.34 (95% CI:1.10–1.62), low paternal education had an OR of 1.42, (95% CI:1.17–1.73), manual labor in the maternal occupation had an OR of 1.31 (95% CI:1.03–1.67), and a history of congenital anomalies in the family had an OR of 1.55 (95% CI:1.19–2.00). Conclusion: This research allowed the identification of epidemiological data and significant risk factors for congenital defects that alter hearing or vision in the population of Bogotá.